Influence of Fluorinated Surfactant Composition on the Stability of Emulsion Drops. Issue 2 (25th October 2016) - Etienne, Gianluca; Kessler, Michael; Amstad, Esther
Abstract : Aqueous drops of a well‐defined size are often used as small containers for conducting chemical and biochemical reactions, cell assays and as templates to produce microparticles. To prevent their coalescence, they must be stabilized, for example, using surfactants. The ability of different nonionic diblock and triblock copolymer surfactants to stabilize water drops that are dispersed in fluorinated oils is compared. In particular, the influence of the length of their hydrophilic poly(ethylene glycol) (PEG) block on the drop stability is studied. The stability of drops coated with triblock copolymers scales with the interfacial tension, whereas that of drops coated with diblock copolymers scales with their packing density. Surfactants whose ratio of the radii of gyration of PEG to the hydrophobic block (FSH) is between 0.54 and 0.67 impart the best stability to aqueous drops containing low salt concentrations. By contrast, surfactants whose ratio of the radii of gyration is between 0.34 and 0.37 impart the best stability to aqueous drops containing high salt concentrations. Hence, the choice of the best surfactant strongly depends on the composition of the fluids. Abstract : The stability of aqueous drops dispersed in fluorinated oils is investigated. The stability of drops coated with triblock copolymers scales with the interfacial tension. By contrast, the stability of drops coated with diblock copolymers scales with their packing density at the liquid–liquid interface.